A Practical Guide on Problem-Solving Teleconsultation in Schools. Issue 2 (3rd April 2023) - King, Hunter C.; Wu, Shengtian; Bloomfield, Bradley S.; Fischer, Aaron J.; Martone, Lauren E.
ABSTRACT: School consultants often use problem-solving consultation when working with educators and caregivers to support the behavioral and academic outcomes of students. Considering some of the well-known limitations to in-person service delivery, consultants have increasingly relied on telecommunications as a medium through which to deliver problem-solving consultation, namely teleconsultation. Thus, this paper serves as a practical guide for school consultants, who work with educators and caregivers, on how to implement each stage of the problem-solving teleconsultation process. With an emphasis given to supports delivered through technology, we provide general guidance and empirically-supported recommendations for how to develop and maintain a strong working alliance with consultees, engage in effective communication practices, strive for equitable practices when collaborating with ethnically and racially diverse populations, monitor treatment progress and deliver performance feedback, and deliver teleconsultation in accordance with state and federal law.